THE FUNCTION OF CRYPTOCURRENCY EVIDENCE IN THE INVESTIGATION PROCESS OF MONEY LAUNDERING CRIME IN THE FRAMEWORK OF CRIMINAL PROCEDURE LAW REFORM - Budiman, Arief; Rusmiati, Elis; Rumin, Mien (Cepalo, 2023)
A cryptocurrency is a new form of Evidence whose existence has not been regulated explicitly and clearly in the Criminal Procedure Code, ITE, and the Money Laundering Law. The problem in this paper is related to the function of electronic currency evidence in the investigation process of money laundering cases. The research method used in this research is normative juridical. The writing stage is carried out through literature searches conducted by examining secondary da, which includes primary legal materials, literature, articles, opinions, experts’ teachings, and their implementation in legislation. When viewed from the Criminal Procedure Code, the Law on Money Laundering, and the Electronic Transactions Information Law, the three cannot be said to accommodate the development of current Evidence. The procedure for investigating and obtaining electronic money evidence should have been regulated in the new Draft Criminal Procedure Code so that formal criminal procedures can be carried out properly.